Challenges in delivery of tuberculosis Services in Ethiopian Pastoralist Settings: clues for reforming service models and organizational structures - Fentabil Getnet; Meaza Demissie; Alemayehu Worku; Tesfaye Gobena; Rea Tschopp; Alinoor Mohamed Farah; Berhanu Seyoum (BMC, 2021)
Abstract Background The End-TB strategy aims to see a world free of tuberculosis (TB) by the coming decade through detecting and treating all cases irrespective of socioeconomic inequalities. However, case detections and treatment outcomes have not been as they should be in Somali pastoral settings of Ethiopia. Hence, this study aimed to explore the challenges that hinder the delivery and utilization of TB services in pastoral areas. Methods A qualitative study was conducted between December 2017 and October 2018 among pastoralist patients with delay of ≥2 months in seeking healthcare, healthcare providers and programme managers. Data were collected from different sources using 41 in-depth interviews, observations of facilities and a review meeting of providers from 50 health facilities. The data were transcribed, coded and analyzed to identify pre-defined and emerging sub-themes. ATLAS.ti version 7.0 was used for coding data, categorizing codes, and visualizing networks. Results Poor knowledge of TB and its services, limited accessibility (unreachability, unavailability and unacceptability), pastoralism, and initial healthcare-seeking at informal drug vendors that provide improper medications were the key barriers hindering the uptake of TB medical services. Inadequate infrastructure, shortage of trained and enthused providers, interruptions of drugs and laboratory supplies, scarce equipment, programme management gaps, lack of tailored approach, low private engagement, and cross-border movement were the major challenges affecting the provision of TB services for pastoral communities. The root factors were limited potential healthcare coverage, lack of zonal and district TB units, mobility and drought, strategy and funding gaps, and poor development infrastructure. Conclusion In pastoral settings of Ethiopia, the major challenges of TB services are limited access, illicit medication practices, inadequate resources, structural deficits, and lack of tailored approaches. Hence, for the pastoral TB control to be successful, mobile screening and treatment modalities and engaging rural drug vendors will be instrumental in enhancing case findings and treatment compliance; whereas, service expansion and management decentralization will be essential to create responsive structures for overcoming challenges.